2017
DOI: 10.1038/s41598-017-13514-w
|View full text |Cite
|
Sign up to set email alerts
|

The circadian transcriptome of marine fish (Sparus aurata) larvae reveals highly synchronized biological processes at the whole organism level

Abstract: The regulation of circadian gene expression remains largely unknown in farmed fish larvae. In this study, a high-density oligonucleotide microarray was used to examine the daily expression of 13,939 unique genes in whole gilthead sea bream (Sparus aurata) larvae with fast growth potentiality. Up to 2,229 genes were differentially expressed, and the first two components of Principal Component Analysis explained more than 81% of the total variance. Clustering analysis of differentially expressed genes identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 83 publications
1
16
1
Order By: Relevance
“…These eurythermal and euryhaline characteristics, in combination with a notable resilience to aquaculture stressors, make this species a rather unique fish with a high plasticity to farming and challenging environments. This adaptation to varying culture conditions has been assessed in a number of physiological studies with focus on nutrition (Benedito-Palos et al, 2016;Simó-Mirabet et al, 2018;Gil-Solsona et al, 2019), chronobiology (Mata-Sotres et al, 2015;Yúfera et al, 2017), feeding behavior (López-Olmeda et al, 2009;Sánchez et al, 2009), stress (Calduch-Giner et al, 2010;Castanheira et al, 2013;Pérez-Sánchez et al, 2013;Bermejo-Nogales et al, 2014;Magnoni et al, 2017;Martos-Sitcha et al, 2017, 2019, or disease resilience (Cordero et al, 2016;Estensoro et al, 2016;Piazzon et al, 2018;Simó-Mirabet et al, 2018). However, the underlying genetic bases of this adaptive plasticity remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…These eurythermal and euryhaline characteristics, in combination with a notable resilience to aquaculture stressors, make this species a rather unique fish with a high plasticity to farming and challenging environments. This adaptation to varying culture conditions has been assessed in a number of physiological studies with focus on nutrition (Benedito-Palos et al, 2016;Simó-Mirabet et al, 2018;Gil-Solsona et al, 2019), chronobiology (Mata-Sotres et al, 2015;Yúfera et al, 2017), feeding behavior (López-Olmeda et al, 2009;Sánchez et al, 2009), stress (Calduch-Giner et al, 2010;Castanheira et al, 2013;Pérez-Sánchez et al, 2013;Bermejo-Nogales et al, 2014;Magnoni et al, 2017;Martos-Sitcha et al, 2017, 2019, or disease resilience (Cordero et al, 2016;Estensoro et al, 2016;Piazzon et al, 2018;Simó-Mirabet et al, 2018). However, the underlying genetic bases of this adaptive plasticity remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of new candidate genes for MAS, particularly for productive traits that are not easy to measure (e.g., feed efficiency, redox homeostasis, intestinal health), can be fueled using wide or targeted transcriptomic approaches (Chen et al, 2011 ; Cardoso et al, 2014 ; Choi et al, 2015 ). The interplay between nutrition and immune system is well recognized; however, the true integration of research on fish nutrition, growth, chronobiology, energy status, immune function and intestinal health is still far from clear despite recent and important advances in this field (Calduch-Giner et al, 2016 ; Estensoro et al, 2016 ; Martin and Król, 2017 ; Piazzon et al, 2017 ; Yúfera et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Light can directly affect the cell growth cycle [2], and light can directly regulate the expression of a biological clock gene per in cells [3]. Further studies have found that the phenomenon of the direct control of circadian clock by light without SCN is common in fish [4,5]. Miki Tanioka et al first found fluctuating biomolecular clocks in the skin of mice [6].…”
Section: Introductionmentioning
confidence: 99%